2020
DOI: 10.3390/su12030901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Participation in Contract Farming on Smallholder Farmers’ Income and Food Security in Rural Benin: PSM and LATE Parameter Combined

Abstract: Investigated in this work is the impact of contract farming participation on smallholder farmers’ income and food security in rice crop production in Northern Benin using 400 randomly selected rice farmer households. Unlike previous studies, we corrected for both observed and unobserved biases by combining propensity score matching (PSM) and the local average treatment effect parameter (LATE). The results showed significant negative consequences of partaking in rice contract farming. We found evidence of signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…This research contributes to the existing literature in two dimensions. First, to our knowledge, most of the previous studies have only focused on comparing farmers’ income in cases such as organic conversion (Doanh et al, 2018 ), farm programs (Pufahl & Weiss, 2008 ), farmers’ training centers (M. Wordofa & Sassi, 2017 ), extension program participation (Attipoe et al, 2021 ), technology adoption (Wordofa et al, 2021a , 2021b ; Wu et al, 2010 ), participation in cooperatives (Dong et al, 2019 ; Tranet al 2021 ; Vuong et al 2021 ), output price support (Abokyi et al, 2020 ), and participation in contract farming (Bezabeh et al 2020 ; Olounlade et al, 2020 ). However, there are no studies to evaluate and compare the income of farming households participating and not participating in ECPs, especially in the context of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research contributes to the existing literature in two dimensions. First, to our knowledge, most of the previous studies have only focused on comparing farmers’ income in cases such as organic conversion (Doanh et al, 2018 ), farm programs (Pufahl & Weiss, 2008 ), farmers’ training centers (M. Wordofa & Sassi, 2017 ), extension program participation (Attipoe et al, 2021 ), technology adoption (Wordofa et al, 2021a , 2021b ; Wu et al, 2010 ), participation in cooperatives (Dong et al, 2019 ; Tranet al 2021 ; Vuong et al 2021 ), output price support (Abokyi et al, 2020 ), and participation in contract farming (Bezabeh et al 2020 ; Olounlade et al, 2020 ). However, there are no studies to evaluate and compare the income of farming households participating and not participating in ECPs, especially in the context of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is impossible to simultaneously measure both Y 1 and Y 0 of a farming household. To overcome this limitation, Olounlade et al ( 2020 ) recommend using the average treatment effect on the treated (ATET). The ATET is expressed in the following mathematical formula: where T = 1 if a farming household is in the participating group and T = 0 if a farming household is in the non-participating group.…”
Section: Methodsmentioning
confidence: 99%
“…The PSM technique has widely been applied in the estimation of impact (Canwat et al , 2020; Iddrisu et al , 2020; Tankam and Djimeu, 2020). However, Olounlade et al (2020) indicate that the PSM is subject to unobserved covariates (conditional independence assumption) which consequently affect the outcome and treatment variables. To control for the hidden bias, Bannor et al (2020a) opine the use of Rosenbaum's analysis of sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Otsuka et al (2016) review focuses on literature in developing countries; they find that although contract farming contributes to the improvement of farmers' income by introducing new crops and production methods, there is room for strengthening its effects on poverty reduction through policy. Olounlade et al (2020) found evidence of significant negative effects on rice production income at a 1% level. The more the rice farmers join in contract farming, the lower the farm income became.…”
Section: Literature Reviewsmentioning
confidence: 96%